Resolving Crustal and Subcrustal Dynamic Sources in Continental Arc Magmas: The Cenozoic Andean Arc of Central Chile - Muñoz Gómez, M. (2025)
The Andean margin of Central Chile (∼32°40′–34°30′S) records abundant Cenozoic arcmagmatic activity with variable compositional characteristics. This is examined through the analysis of anextensive database of new and published whole‐rock geochemistry and Sr‐Nd isotopic compositions, in additionto zircon Hf and O isotopic compositions. The whole‐rock data record an increasing assimilation of continentalcrust material that developed through the compressional regime set in the margin in the Early Miocene that ledto the construction of the modern Andes. The same is recorded by the Hf and O isotopic compositions, but thesealso allow identification of components involved in the magma genesis: (a) the sub arc mantle derived primarymagmas, (b) a late Paleozoic—Early Triassic crystalline component, as that currently outcropping immediatelyto the east of the study area, (c) a deep enriched component, which likely corresponds to the Cuyania terrane, aGrenville age basement recognized further east in this Andean region, and (d) a deep juvenile low‐δ18Ocomponent, interpreted here as basement with oceanic crust affinities. This latter component reveals a possiblecomposite nature for the Chilenia terrane, the postulated Grenville age basement in the region. The CenozoicAndean arc magmas correspond to the differentiated products of an extensive intra‐crustal re‐working, takingplace along tens of kilometers below their emplacement level, and whose main imprint is on the magmaticisotopic composition. Our results document the role of the continental crust, particularly regarding its evolvingarchitecture and constitution, over the composition of arc magmas.